PENGARUH WAKTU ULTRASONIKASI TERHADAP KARAKTERISTIK FISIKA NANOPARTIKEL KITOSAN EKSTRAK ETANOL DAUN SUJI (Pleomele angustifolia) DAN UJI STABILITAS FISIKA MENGGUNAKAN METODE CYCLING TEST - Malinda Prihantini; Elya Zulfa; Listyana Dewi Prastiwi; Ikha Dyah Yulianti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACT The nanoparticle system encapsulates and protects flavonoids of suji leaves from photolysis and oxidation instability. Chitosan is a biocompatible, biodegradable and non-toxic nanoparticles forming polymer. Ultrasonication is a materials mixing technique under high vibration energy. The ultrasonication time affects the particle size. The aim of this study was to determine the effect of the ultrasonication time on physical characteristics of chitosan nanoparticles of suji (Pleomele angustifolia) leaf ethanol extract and its physical stability after cycling test. Ethanol extract of suji leaves (EEDS) was obtained by maceration using 70% ethanol. Chitosan EEDS nanoparticles were made under ionic gelation method using an ultrasonication time of 3 minutes (FI), 6 minutes (FII), and 9 minutes (FIII). The physical characterization of nanoparticles includes particle size, polydispersity index, and zeta potential. Chitosan EEDS nanoparticles with the best physical characteristics (FIII) were tested for stability using cycling test method. The data obtained were analyzed using the Anova statistical method with a 95% confidence level. The size of EEDS chitosan nanoparticles (nm) was significantly different in all formulas, FI (374.47), FII (288.43), and FIII (233.37). The polydispersity index of FI (0.38) and FIII (0.65) were significantly different, while FII (0.41) was not significantly different. The zeta potential (mV) FI (51.70), FII (46.10), and FIII (48.60) were not significantly different in all formulas. The physical characteristics of Formula III after Cycling Test showed a particle size of 455.0 nm, a polydispersity index of 0.174, and a zeta potential of 20.1 mV. Keywords: ultrasonication, nanoparticles, chitosan, cycling test, suji leaf (Pleomele angustifolia)